A Simultaneous-Equation Model of Estimating Exchange Rate Pass-Through in Malaysia - Yu Hsing (Yayasan Ahmar Cendekia Indonesia, 2020)
Based on an extended IS-LM-AS model, this study finds that a 1% depreciation of the Malaysian ringgit tends to cause the CPI to rise by 0.1194%. Moreover, more M2 money supply, a lower government borrowing as a percent of GDP, a higher crude oil price, a higher U.S. CPI, and a higher expected consumer price index tend to raise Malaysia’s CPI. Therefore, exchange rate pass-through (ERPT) to the consumer price in Malaysia is partial and incomplete.